2005
DOI: 10.1016/j.nds.2004.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Data Sheets for A = 155

Abstract: A b s t r a c t : T h i s w o r k r e p r e s e n t s a n u p d a t e o f t h e p r e v i o u s e v a l u a t i o n o f t h e n u c l e a r d a t a o n t h e A = 1 5 5 n u c l i d e s (1994Re10). The experimental data from reaction and decay studies leading to these nuclides have been reviewed.T h e e l e m e n t s i n c l u d e d r a n g e f r o m C e ( Z = 5 8 ) t h r o u g h T a ( Z = 7 3 ) . T h e s e d a t a a r e s u m m a r i z e d a n d p r e s e n t e d , together with the adopted level schemes and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 217 publications
5
18
1
Order By: Relevance
“…As shown in Fig. 4, the X(3/4) model also agrees well with the experimental results of 155 Tb [38], which was also chosen as the X(5/2j+1) model candidate in [30]. The present X(3/2j+1) results seem little better in quantity than those of the X(5/2j+1) model shown in [30].…”
Section: Comparison With Experimental Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…As shown in Fig. 4, the X(3/4) model also agrees well with the experimental results of 155 Tb [38], which was also chosen as the X(5/2j+1) model candidate in [30]. The present X(3/2j+1) results seem little better in quantity than those of the X(5/2j+1) model shown in [30].…”
Section: Comparison With Experimental Resultssupporting
confidence: 80%
“…Firstly, the collective 3/2 + 2 and 1/2 + 1 levels based on the ground state in the theory are not observed in experiment. Two levels with (1/2 + , 3/2 + , 5/2 + ) at 508.395 keV and (3/2 + , 5/2 + , 7/2 + ) at 517.542 keV observed in the experiment [38] are noticeably too higher to be the two states predicted based on the ground state in the theory. Secondly, the 9/2 + 1 and 13/2 + 1 levels from the X(3/4) model are also noticeably higher than those observed in experiment.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 60%
“…The placement suggested in our measurement is also presented in this table (indicated by the desexcitation energy level); a decay scheme is shown in Fig.1. Two γ-transitions at 205.7keV and 224.8keV were observed for the first time in beta decay studies, but our data revealed no evidence for photopeaks at: 53, 63, 65, 80, 90, 183, 220, 280, 665, 758, 818, 830, 861, 880, 911, 1018 and 1096keV, observed in previous works [1][2][3]11]. We could not calculate the upper intensity limits [12] of these unobserved gamma rays due to proximity of them to a lot of γ-transitions following 155 Sm decay.…”
Section: Resultscontrasting
confidence: 72%
“…The measured gamma-ray energies and relative intensities are listed in Table I and compared with the last compilation performed by Reich [11]. The placement suggested in our measurement is also presented in this table (indicated by the desexcitation energy level); a decay scheme is shown in Fig.1.…”
Section: Resultsmentioning
confidence: 93%
“…Figure 5 shows the yields measured for the most volatile Ln isotopes released without fluorination by UC x pellets heated at ∼ 2050 • C. The spectroscopic data required to extract the yields from the γ spectra, in particular the half-lives and the absolute γ intensities, were taken from refs. [16][17][18][19][20]. This result proves that the Ln photo-fission cross sections are sufficient to allow the observation of Ln mass-separated ion beams provided that the target temperature is high enough.…”
Section: From the Off-line Testssupporting
confidence: 52%